(untitled) (International Journal of Current Engineering and Technology, 2015)
The Variable Valve Systems (VVS) are emerging to exploit benefits towards improving gasoline-engine fuel economy and reducing emission. Such systems control the area, time and duration of cylinder opening. Literature review indicates that VVS are treated as an extension of existing engine valve by adding control elements in the existing system. However, extensions make valve systems complex, bulky and require additional cost. Therefore, their applications tend to be limited. This paper presents the design of variable valve systems using innovative-tribo-design concept that provides a systematic and scientific procedure. This concept provides future direction and enhances designers’ creativity. The innovative-tribo-design approach is demonstrated to establish it as a comparator for upcoming variable valve systems (VVS).